2009
DOI: 10.1007/s00221-009-1714-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional subdivisions in low-frequency primary auditory cortex (AI)

Abstract: We wished to test the hypothesis that there are modules in low-frequency AI that can be identified by their responsiveness to communication calls or particular regions of space. Units were recorded in anaesthetised guinea pig AI and stimulated with conspecific vocalizations and a virtual motion stimulus (binaural beats) presented via a closed sound system. Recording tracks were mainly oriented orthogonally to the cortical surface. Some of these contained units that were all time-locked to the structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…The rhythmic structure of the sound bursts in the purr call may also be important in permitting a prolonged timelocked response because recent work in the ferret has shown that the temporal envelope of a complex sound may act in gating the analysis of fine structure at up to a few hundred Hz (Elhilali et al, 2004). We have previously suggested that the responses to the purr stimulus are organized in a columnar fashion (Wallace et al, 2005;Wallace and Palmer, 2009) and our previous results (Wallace et al, 2002) indicate that there is at least a partial overlap between the cells that phase-lock to pure tones and those that accurately represent the structure of the purr. However, there is not a one-to-one correspondence as we were able to record units that gave a strong, time-locked response to the purr call but did not phase-lock to pure tones.…”
Section: Significance Of Phase-locking In the Cortexmentioning
confidence: 98%
See 4 more Smart Citations
“…The rhythmic structure of the sound bursts in the purr call may also be important in permitting a prolonged timelocked response because recent work in the ferret has shown that the temporal envelope of a complex sound may act in gating the analysis of fine structure at up to a few hundred Hz (Elhilali et al, 2004). We have previously suggested that the responses to the purr stimulus are organized in a columnar fashion (Wallace et al, 2005;Wallace and Palmer, 2009) and our previous results (Wallace et al, 2002) indicate that there is at least a partial overlap between the cells that phase-lock to pure tones and those that accurately represent the structure of the purr. However, there is not a one-to-one correspondence as we were able to record units that gave a strong, time-locked response to the purr call but did not phase-lock to pure tones.…”
Section: Significance Of Phase-locking In the Cortexmentioning
confidence: 98%
“…In our recent study of AI(LF) (Wallace and Palmer, 2009) we suggested that there may be 8 or 9 functional columns e each with a diameter of about 500 mm. These columns were defined in terms of responses to conspecific vocalizations or sensitivity to interaural phase differences.…”
Section: Columnar Arrangement Of Phase-locked Responsesmentioning
confidence: 98%
See 3 more Smart Citations